Nano-battery technology for EV-HEV panel: a pioneering study - Rahman, Mohammed Ataur; Rashid, Muhammad Mahbubur; Mohiuddin, A. K. M.; Hawlader, Mohammad Nurul Alam (IIUM Press, 2015)
Global trends toward CO2 reduction and resource efficiency have significantly increased the importance of lightweight materials for automobile original equipment manufacturers (OEM). CO2 reduction is a fundamental driver for a more lightweight automobile. The introduction of Electrical Vehicles (EVs) is one initiative towards this end. However EVs are currently facing several weaknesses: limited driving range, battery pack heaviness, lack of safety and thermal control, high cost, and overall limited efficiency. This study presents a panel-style nano-battery technology built into an EV with CuO filler solid polymer electrolyte (SPE) sandwiched by carbon fiber (CF) and lithium (Li) plate. In addition to this, an aluminum laminated polypropylene film is used as the electromagnetic compatibility (EMC) shield. The proposed battery body panel of the EV would reduce the car weight by about 20%, with a charge and discharge capacity of 1.5 kWh (10% of car total power requirement), and provide the heat insulation for the car which would save about 10% power consumption of the air conditioning system.Therefore, the EV would be benefited by 30% in terms of energy reduction by using the proposed body. Furthermore, the proposed body is considered environmental-friendlysince it is recyclable for use in a new product. However, the main limiting factors of the SPE are its thermal behavior and moderate ionic conductivity at low temperatures. The SPE temperature is maintained by controlling the battery panel charging/discharge rate. It is expected that the proposed panel-style nano-battery use in an EV would save up to6.00 kWh in battery energy, equivalent to 2.81 liters of petrol and prevent 3.081 kg of CO2 emission for a travel distance of 100 km.